Impact of Akhlaq Self-Regulation and Self-Regulated Learning on Performance in Islamic Education Course Among Premier Polytechnic Students - A. Shukor, Khairunnisa (2013)
The literature suggests that religion fosters self-regulation producing a person who possesses magnificent akhlaq. This study aims to identify the self-regulation aptitude in the context of behavior (akhlaq self-regulation, AS) and academic (self-regulated learning, SRL), and the relationship between these two constructs and academic performance in the Islamic Education course among premier polytechnic students in Malaysia. On the basis of a self reported questionnaire, the data were obtained from 341 students studying Islamic Education course at the three premier polytechnics in Malaysia. The questionnaire consists of demographic information of the students, AS and SRL. Statistical Software for Social Sciences (SPSS) Version 19.0 was used to quantitatively analyse the students' responses to the constructs. The results of the research show that the levels of AS in personal, social, and religious affairs are high with the overall mean score of 3.89, 3.91 and 4.27 consecutively, while the levels of SRL in in terms of motivation is high with the overall mean score of 3.77 and learning strategies is average with the overall mean score of 3.40. The level of academic performance in the Islamic Education course is shown to be at the average with the overall mean score of 2.62. The results show that AS in personal affairs, organization, time study environmental management have weak positive relationships with academic performance in the Islamic Education course (rs ranged between .111 to .137), and control of learning beliefs and test anxiety have weak negative relationships with academic performance in the Islamic Education course (rs ranged between -.110 to -.167). The findings demonstrate low to very strongly relationships between the constructs of AS and the constructs of SRL (rs ranged between -.110 to .841). Overall, students who observe the AS in personal affairs, have moderate control of learning beliefs and anxiety, academically organized and able to manage time and study environment are relatively able to perform higher than other students who don't. Even though the impact of akhlaq and academic self regulation on academic performance is shown to be low, the increase of students' AS leads to an increase of SRL, thus it implies that the more students behave according to the akhlaq imposed in the Quran, the more students able to control the way they learn the Islamic Education course. The study concludes with a discussion of practical and theoretical implications of the findings along with suggestions for future research.